“ROLE OF COMPUTED TOMOGRAPHY BRAIN IN ESTABLISHING THE FREQUENCY OF DIFFERENT TYPES AND SUBTYPES OF STROKE AND TO CORRELATE THEM WITH RISK FACTORS AND TIME OF ONSET OF SYMPTOMS AND OUTCOME - Iram Javeed; Nayab Alia; Adeen Akram (Journal of University Medical & Dental College, 2017)
ABSTRACT: Objectives: This study was performed to establish role of CT Brain in establishing frequency of different type and subtypes of stroke in Pakistani population and to correlate CT findings with risk factors and duration of onset of symptoms that lead patient to take admission in hospital and outcome of different types of stroke. Methodology: A sample of hundred patients was taken from SOCIAL SECURITY HOSPITAL MULTAN ROAD LAHORE over a period of nine months starting from October 2014 to June 2015.A prospective study with convenient sampling technique was performed. Equipment used was 64 slice TOSHIBA CT scanner machine. Patients with incomplete data, pediatric age group to age 14 years, stroke due to trauma, infections or tumours were excluded from this study. A detailed questionnaire was used to collect data from the patients that included age, sex, type of stroke, time of onset of symptoms, location of lesion on CT brain, odema of cerebral tissues, midline shift predisposing risk factors like HTN, DM, oldage, high cholesterol levels, CLDetc and outcome of stroke and time of death in some cases was recorded.The collected data was analyzed by SPSS-20. Results: Shows that infarctive stroke was more prevalent type of stroke in Pakistani population and the frequency increases with increasing age and stroke was more prevalent in men than in women.It shows that subdural hematomas were more prevalent out of hemorrhagic strokes than other subtypes of extraaxial type of hemorrhagic strokes.Complications like odema of cerebral tissues,midline shift and disabilities were more common in hemorrhagic strokes than in infarctive strokes.Also the cases of stroke due to rupture of a blood vessel presented earlier to hospital because of early onset of symptoms as compared to cases of stroke due to blockade of a blood vessel.